Efficacy of tart cherry juice in reducing muscle pain during running: a randomized controlled trial - Elliot Diane L; Perrier Erica T; Kuehl Kerry S; Chesnutt James C (Taylor & Francis Group, 2010)
Abstract Background Long distance running causes acute muscle damage resulting in inflammation and decreased force production. Endurance athletes use NSAIDs during competition to prevent or reduce pain, which carries the risk of adverse effects. Tart cherries, rich in antioxidant and anti-inflammatory properties, may have a protective effect to reduce muscle damage and pain during strenuous exercise. This study aimed to assess the effects of tart cherry juice as compared to a placebo cherry drink on pain among runners in a long distance relay race. Methods The design was a randomized, double blind, placebo controlled trial. Fifty-four healthy runners (36 male, 18 female; 35.8 ± 9.6 yrs) ran an average of 26.3 ± 2.5 km over a 24 hour period. Participants ingested 355 mL bottles of tart cherry juice or placebo cherry drink twice daily for 7 days prior to the event and on the day of the race. Participants assessed level of pain on a standard 100 mm Visual Analog Scale (VAS) at baseline, before the race, and after the race. Results While both groups reported increased pain after the race, the cherry juice group reported a significantly smaller increase in pain (12 ± 18 mm) compared to the placebo group (37 ± 20 mm) (p < .001). Participants in the cherry juice group were more willing to use the drink in the future (p < 0.001) and reported higher satisfaction with the pain reduction they attributed to the drink (p < 0.001). Conclusions Ingesting tart cherry juice for 7 days prior to and during a strenuous running event can minimize post-run muscle pain.